Antiviral Responses in Cancer: Boosting Antitumor Immunity Through Activation of Interferon Pathway in the Tumor Microenvironment - Vitiello, Glauco Akelinghton Freire; Ferreira, Wallax Augusto Silva; Cordeiro de Lima, Vladmir Cláudio; Medina, Tiago da Silva (Frontiers in Immunology, 2021)
In recent years, it became apparent that cancers either associated with viral infections or aberrantly expressing endogenous retroviral elements (EREs) are more immunogenic, exhibiting an intense intra-tumor immune cell infiltration characterized by a robust cytolytic apparatus. On the other hand, epigenetic regulation of EREs is crucial to maintain steady-state conditions and cell homeostasis. In line with this, epigenetic disruptions within steady-state cells can lead to cancer development and trigger the release of EREs into the cytoplasmic compartment. As such, detection of viral molecules by intracellular innate immune sensors leads to the production of type I and type III interferons that act to induce an antiviral state, thus restraining viral replication. This knowledge has recently gained momentum due to the possibility of triggering intratumoral activation of interferon responses, which could be used as an adjuvant to elicit strong anti-tumor immune responses that ultimately lead to a cascade of cytokine production. Accordingly, several therapeutic approaches are currently being tested using this rationale to improve responses to cancer immunotherapies. In this review, we discuss the immune mechanisms operating in viral infections, show evidence that exogenous viruses and endogenous retroviruses in cancer may enhance tumor immunogenicity, dissect the epigenetic control of EREs, and point to interferon pathway activation in the tumor milieu as a promising molecular predictive marker and immunotherapy target. Finally, we briefly discuss current strategies to modulate these responses within tumor tissues, including the clinical use of innate immune receptor agonists and DNA demethylating agents.